Current and Voltage Mode Multiphase Sinusoidal Oscillators Using CBTAs - Sagbas, Mehmet; Ayten, Umut Engin; Herencsar, Norbert; Minaei, Shahram (SPOLECNOST PRO RADIOELEKTRONICKE INZENYRSTVI, 2013)
Current-mode (CM) and voltage-mode (VM) multiphase sinusoidal oscillator (MSO) structures using current backward transconductance amplifier (CBTA) are proposed The proposed oscillators can generate n current or voltage signals (n being even or odd) equally spaced in phase. n+1 CBTAs, n grounded capacitor and a grounded resistor are used for nth-state oscillator. The oscillation frequency can be independently controlled through transconductance (g) of the CBTAs which are adjustable via their bias currents. The effects caused by the non-ideality of the CBTA on the oscillation frequency and condition have been analyzed. The performance of the proposed circuits is demonstrated on third-stage and fifth-stage MSOs by using PSPICE simulations based on the 0.25 mu m TSMC level-7 CMOS technology parameters.
Keywords: Multiphase sinusoidal oscillator; current backward transconductance amplifier (CBTA); current-mode circuits; voltage-mode circuits; active networks; FILTERS; Engineering